Let's simplify each expression step by step.
-
\(\sqrt{36} + \sqrt{221}\)
\(\sqrt{36} = 6\)
\(\sqrt{221} \approx 14.87\) (since 14.87 * 14.87 ≈ 221)
Thus,
\[ \sqrt{36} + \sqrt{221} = 6 + 14.87 \approx 20.87 \] -
\(\pi + \sqrt{4}\)
\(\sqrt{4} = 2\)
Therefore,
\[ \pi + \sqrt{4} = \pi + 2 \approx 3.14 + 2 \approx 5.14 \] -
\(0.643892553...\ + \frac{3}{4}\)
Since \(\frac{3}{4} = 0.75\), we now add:
\[ 0.643892553... + 0.75 \approx 1.393892553... \] -
\(0.6\overline{6} + 9\) (where \(0.6\overline{6} = \frac{2}{3}\))
First, recognize \(0.6\overline{6}\) is equal to \(\frac{2}{3}\). So we have:
\[ \frac{2}{3} + 9 = 9 + 0.666... \approx 9.666... \]
So, to summarize:
- \(\sqrt{36} + \sqrt{221} \approx 20.87\)
- \(\pi + \sqrt{4} \approx 5.14\)
- \(0.643892553... + \frac{3}{4} \approx 1.393892553...\)
- \(0.6\overline{6} + 9 \approx 9.666...\)